Qualitative responses to Hydrogen Homes (H2H) Online Survey 2022.docx - Gordon, Joel; Balta-Ozkan, Nazmiye; Nabavi, Seyed Ali (Cranfield University, 2024)
This file records responses given by online survey participants in the UK (N = 1845) to a questionnaire on the domestic hydrogen transition, which was programmed using Qualtrics. The data collection period lasted between 06/10/2023 and 23/12/2023, supported by a professional market research company (Savanta). The survey duration was approximately 15 to 20 minutes. Domestic hydrogen refers to hydrogen-fuelled appliances for heating and cooking, collectively referred to as hydrogen homes. All survey responses were measured using either a five-point or eleven-point Likert scale.At the end of the survey, participants were requested to respond to the following open-ended question which concluded the survey: Please use this text box to explain more about your attitudes towards hydrogen or any other reflections on this topic.Around two-thirds of respondents (N = 1213) provided a valid response. The sample was composed of four specific consumer sub-groups, which returned a relatively balanced response rate (M = 66.3%; SD = 3.0). In published materials, we use the term Hydrogen Homes (H2H) dataset to denote outputs from this project.
Keywords: 'Hydrogen acceptance'; 'Consumer attitudes'; 'Low-carbon heating and cooking'; 'Fuel Stress'; 'Technology and environmental engagement'; 'Net Zero Energy'; 'Hydrogen economy'; 'Hydrogen homes'